Antifungal Potential of Organic Acids Produced by Mortierella Alpina - N. Shemshura, Olga; N. Shemsheyeva, Zhazira; K. Sadanov, Amankeldy; Lozovicka, Bozena; V. Kamzolova, Svetlana; G. Morgunov, Igor (International Journal of Engineering and Technology, 2018)
The effect of metabolites is synthesized by M. alpina for growth and the synthesis of mycotoxins was studied using phytopathogenic fungi Purpureocillium lilacinum, Fusarium tricinctum and Fusarium oxysporum on infected rhizosphere and seeds of alfalfa cultivars. It was found that culture filtrate medium is suppressed into colony formation of phytopathogenic fungi from 56 to 96%. Arachidonic acid inhibits the growth of F. tricinctum and F. oxysporum by 69 to 90%, respectively, and enhanced by 62% in P. lilacinum. Moreover, arachidonic acid was found to be active inhibitor to the synthesis of mycotoxins by phytopathogenic fungi: in the presence of arachidonic acid F. oxysporum and F. tricincium do not synthesize zearalenone, and P. lilacinum - roquefortine and fellutanine. Â